The Osmanthus fragrans flower phenylethanoid glycoside-rich extract: Acute and subchronic toxicity studies. (1st July 2016) - Lu, Baiyi; Li, Maiquan; Zhou, Fei; Huang, Weisu; Jiang, Yirong; Mao, Shuqin; Zhao, Yajing; Lou, Tiantian
Abstract: Ethnopharmacological relevance: Osmanthus fragrans var. thunbergii ( O. fragrans ) flower has been consumed as folk medicine for thousands of years. O. fragrans flower extract is a well-characterized phenylethanoid glycoside-rich extract, which has been used as a natural anti-oxidant. The aim of this study was to evaluate the safety of O. fragrans flower phenylethanoid glycoside-rich extract (OFFE). Materials and methods: The OFFE was extracted by 80% (v/v) aqueous ethanol with 0.01% sodium isoascorbate (w/v) from the O. fragrans flower and purified on HPD300 resins. The total phenylethanoid glycosides content and individual phenylethanoid glycosides was determined by photocolorimetric method and reversed phase UPLC respectively. An acute oral toxicity study, reverse mutation test, bone marrow cell micronucleus test, and sperm abnormality test as well as a 90-day oral toxicity study were performed on experimental animals. Results: The total content of phenylethanoid glycosides in OFFE was 73.4 g acteoside equivalent per 100 g of extract, include acteoside (52.5 g per 100 g of extract), salidroside (13.8 g per 100 g of extract), and isoacteoside (2.6 g per 100 g of extract) and so on. No acute lethal effect at the maximal tested OFFE dose of 10 g/kg body weight (bw) in either rats or mice was observed, suggesting that OFFE can be considered nontoxic. No evidence for mutagenicity was detected in any of the three mutagenic tests. Administration at levels of 0.50, 1.00, and 2.00 g/kg bw to rats for 90 days failed to induce any significant hematological, clinical, chemical, or histopathological changes. The no-observed adverse-effect-level for OFFE was >2.00 g/kg bw for the study on subchronic toxicity. Conclusion: The results showed that consuming OFFE has no adverse effects and poses no health risk in the acute oral toxicity study, subchronic oral toxicity study, and in the micronucleus test, which may provide supportive evidence for the safety of OFFE powder that has been used in medicine as well as in functional foods, and dietary supplements. Graphical abstract: